Identifikasi Potensi Alam Berbasis Geo-Edukasi di Desa Dulangeya Provinsi Gorontalo - Noviar Akase; Muh Kasim; Mutiara Nonsi; Irmawati Irmawati; Moh. Nazer Ismail; Irene Ester Wowiling (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2022)
The location of the implementation of community service is located in Dulangeya Village, Botumoito District, Boalemo Regency, Gorontalo Province. The purpose of this service activity is to increase public knowledge and awareness about the natural potential that exists in Dulangeya Village, so that the positive impact of the natural potential can be optimized and the negative impact can be minimized. The implementation of the activity goes through 3 (three) stages, namely the preparation and planning stage, the Socialization stage for the Service Work Program and the last is the Work Program Implementation stage. The model used is in the form of Geo-Education which contains Socialization and Counseling, and the manufacture of Information Boards. This service activity has been carried out well. proven to be able to increase the knowledge and understanding of rural communities in utilizing and conserving natural potential. The return of public awareness to always clean hot spring pools, then the implementation of disaster mitigation in the field of early childhood education is able to increase children's understanding of disasters around them, as well as the realization of the sustainability of a generation that is resilient to disasters